Green Politics and Parties: Strategies for internalising Green Politics in Indonesia - Septian Noor, Rico; Kristanto, Kiki; Yestati, Ariani; Jalianery, Joanita; Evi (Pandecta Research Law Journal, 2025)
This study aims to put forward the idea of a strategy for internalising Green Politics in Indonesia by looking at good practices in other countries such as the practice of green party campaigns in Australia and the presence of Green Parties in Germany. This study uses Qualitative research. This method was chosen to analyse and deeply explore important issues related to Green Politic in this study. This study concludes that there are 2 (two) efforts to internalise Green Politic in Indonesia, namely First, by initiating an environment-based social movement into political parties in Indonesia such as the practice carried out by the Indonesian Forum for the Environment (WALHI) by looking at the good practices of the Green campaign in Australia and the second is the idea of internalising Green Politic through the formation of Green Parties in Indonesia such as the practice of green parties in Germany with the hope that these two efforts can make changes, especially in efforts to do justice in the environmental field through the process of formulating policies that are in favour of environmental issues in Indonesia.